Students' Perception of the Use of Snowball Throwing Technique in Teaching Reading Skill - A. Dian Islamiati; Syarifuddin Dollah; Geminastiti Sakkir (ARRUS Journal of Social Sciences and Humanities, 2024)
This study aims to describe the perceptions of class VIII A students at MTs Negeri 1 Sidrap on the use of the snowball throwing technique in teaching reading skill. This research design uses quantitative research methods. The sample of this study was 25 students in class VIII A as experimental group, samples were taken using cluster random sampling techniques. Data collection through questionnaires. The researcher used a questionnaire to measure students’ perception. The questionnaire that the researcher used 2 types of questions in the questionnaire are positive questionnaire and negative questionnaire, 10 positive questions and 10 negative questions. From the results of the questionnaire, the students' perceptions regarding the use of the snowball throwing technique were positive perceptions to the students.